The Long Road to Partnership: Conﬂict Resolution of Register 45 Mesuji Lampung - Komang Jaka Ferdian; Hieronymus Soerjatisnanta (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
A known agrarian issue took place in Indonesia, particularly in the area of Register 45 Mesuji Lampung. The granting of natural forest management permit by the government to PT. Silva Inhutani, thus eliminating public access around Register 45 to manage the forest, subsequently lead to conﬂict in the region. The objectives of this research are, namely: 1) to explain the grounds for partnership in the Register 45 area; and 2) to analyze the partnership program undertaken in Register 45 as an eﬀort of resolving conﬂict. This research used a descriptive qualitative approach that describes the results of research, assessment and other references reinforced with empirical data through interviews and observations. This study found a number of issues in the partnership agreement formation process, wherein the community was not being involved in the formation process of the partnership provisions, such as the planting process and the proﬁt sharing scheme. The issues found in the implementation stage of the partnership agreement can be observed from an internal factor perspective, which was the unfulﬁlled expectation to increase acacia planting. Regarding the external factor, there were still many acts of thuggery in the area of Register 45 that interfered with the partnership process. There was also a fundamental problem in the partnership implementation, which was the prevalent lack of aptness in the mapping of community entitled to the partnership, as well as the lack of trust among collaborating parties.